Novgorod and Vladimir periods activities of Prince Roman Mstislavovich in the scientific research of Oleksandr Golovko - Чугуй, Т. (Київський національний університет імені Тараса Шевченка, 2025)
The relevance is due to the fact that at the current stage, there is no thorough study of the contribution of O. Holovko to the study of the Novgorod and Volodymyr periods of the reign of Roman Mstyslavovych in historiography. The study of the activities of Prince Roman in the works of the scientists is an integral part of the development of the topic of the role of the Romanovych dynasty in the processes of state formation in Ukraine. The personality of Prince Roman is given due attention in the context of the development of Rus'-Polish relations in the second half of the 12th - early 13th centuries. The researcher developed a new concept of the history of Ukraine in the mediaeval period, highlighting the process of the development of the first state formations in the territory of Volhynia and Precarpathia, the evolution of these regions as part of Ancient Rus', and the formation of principality lands in the period of disunity. The purpose of the article is to consider the scientific achievements of O. Golovko regarding the restoration of the Novgorod and Volodymyr periods of Roman Mstislavovych's activity, using the source base and literature. Conclusions. O. Holovko devoted a lot of attention to the study of the Novgorod and Volodymyr periods of Roman Mstyslavych's activity, becoming one of the leading researchers of this issue. A characteristic feature of the scientist's scientific works is that they are written based on the processing of a great number of sources and literature. He made correct conclusions regarding the reasons for the prince's transition to Volodymyr, the transformation of political influences in the Volyn land during the 1170s–1180s, the coverage in the sources of the campaign of Casimir II the Just to Berestia in 1181–1182, the political relations of Volodymyr and Halych with Poland, Hungary, and the Holy Roman Empire in 1188–1189, and the consequences of the battle on the Mozgava River in 1195. Research on the life path of Prince Roman, carried out by O. Holovko, is important for the further development of the scientific topic about the role of the Romanovych dynasty in the processes of the history of state formation in Ukraine.

Актуальність зумовлена тим, що на сучасному етапі в історіографії відсутнє ґрунтовне дослідження внеску О. Головка у вивчення новгородського і володимирського періодів правління Романа Мстиславовича. Дослідження діяльності князя Романа у роботах вченого є складовою частиною розробки теми про роль династії Романовичів у процесах державотворення України. Особистості князя Романа приділено належну увагу в контексті розвитку русько-польських відносин другої половини ХІІ – початку ХІІІ ст. Дослідник розробив нову концепцію історії України середньовічної доби, висвітливши процес розвитку перших державних утворень на території Волині й Прикарпаття, еволюцію цих регіонів у складі Давньої Русі та формування земель-князівств в удільну добу. Метою статті є розгляд на основі джерельної бази і літератури наукових досягнень О. Головка щодо відновлення новгородського і володимирського періодів діяльності Романа Мстиславовича. Висновки. О. Головко присвятив вивченню новгородського і володимирського періодів діяльності Романа Мстиславовича багато уваги, ставши одним із провідних дослідників цього питання. Характерною ознакою наукових праць вченого є те, що вони написані на основі опрацювання великого масиву джерел і літератури. Вірні висновки він зробив щодо причин переходу князя до Володимира, трансформації політичних впливів на Волинській землі упродовж 70–80-х років ХІІ ст., висвітлення у джерелах походу Казимира ІІ Справедливого на Берестя в 1181–1182 рр., політичних відносин Володимира і Галича з Польщею, Угорщиною й Священною Римською імперією в 1188–1189 рр., наслідків бою на р. Мозгава 1195 р. Дослідження життєвого шляху князя Романа, здійснені О. Головком, є важливими для подальшої розробки наукової теми про роль династії Романовичів у процесах історії державотворення України.
Новгородський і Володимирський періоди діяльності князя Романа Мстиславовича у наукових дослідженнях Олександра Головка